Improvements in tissue blood flow and lumbopelvic stability after lumbopelvic core stabilization training in patients with chronic non-specific low back pain - Aatit Paungmali (2018)
© 2016 The Society of Physical Therapy Science. Published by IPEC Inc. [Purpose] This study investigated the effects of lumbopelvic stabilization training on tissue blood flow changes in the lumbopelvic region and lumbopelvic stability compared to placebo treatment and controlled intervention among patients with chronic non-specific low back pain. [Subjects and Methods] A total of 25 participants (7 males, 18 females; mean age, 33.3 ± 14.4 years. participated in this within-subject, repeated-measures, doubleblind, placebo-controlled comparison trial. The participants randomly underwent three types of interventions that included lumbopelvic stabilization training, placebo treatment, and controlled intervention with 48 hours between sessions. Lumbopelvic stability and tissue blood flow were measured using a pressure biofeedback device and a laser Doppler flow meter before and after the interventions. [Results] The repeated-measures analysis of variance results demonstrated a significant increase in tissue blood flow over the lumbopelvic region tissues for post- versus pre-lumbopelvic stabilization training and compared to placebo and control interventions. A significant increase in lumbopelvic stability before and after lumbopelvic stabilization training was noted, as well as upon comparison to placebo and control interventions. [Conclusion] The current study supports an increase in tissue blood flow in the lumbopelvic region and improved lumbopelvic stability after core training among patients with chronic nonspecific low back pain.